Crocin Monotherapy in Non-Central Diabetic Macular Edema - Mojtaba Mojtahedzadeh; Masoud Reza Manaviat; Seyed Reza Mirjalili; Adeleh Sahebnasagh; Mohammad Khan Ardani; Farahnaz Hoseinzadeh; Fatemeh Saghafi (Journal of Pharmaceutical Care)
Background: Crocin can be utilized as an anti-inflammatory component of Saffron in diabetic macular edema (DME), which is known as the most common cause of vision loss in patients with diabetes mellitus (DM). Although anti-vascular endothelial growth factor (VEGF) agents are common in non-center involving DME (NCI-DME), there is no consensus on NCI-DME treatment. Methods: This before-after study was performed from October 2019 to August 2021. Twenty-six eyes of 16 patients with type 2 DM in Baghayipoor Clinic in Yazd, were treated with 15 mg crocin per day for 90 days. Patients had at least one eye with non-proliferative DR (NPDR) and NCI-DME along with no adherence to intravitreal injection or a contraindication of intravitreal injection. Central subfield thickness (CST), visual acuity, fasting blood sugar (FBS), and HbA1c were assessed once before and once after the study (day 90). Results: After 90 days of therapy, the mean CST significantly decreased to 2.8 μm (P-value=0.030), four patients had increased CST and 1 patient had a significantly decreased CST (≥25μm). The mean Logarithmic Minimum angle of resolution increased during the study. The Mean (±SD) FBS showed a significant improvement during the study from 174.7 (±60.41) at baseline up to 161.8 (±47.7) at day 90 (P-value = 0.012). HbA1c had no significant reduction. Nausea/vomiting and insomnia were among the reported adverse effects. Nevertheless, no one withdrew from the study because of the adverse effects. Conclusion: This study suggests Crocin’s positive impact on NCI-DME. It may also improve the glycemic profile of diabetic patients; however, more high-quality randomized clinical trials with larger sample sizes and longer durations are needed for validation.